Immunological findings associated with Argentinean strains of Mycobacterium avium subsp. paratuberculosis in bovine models - Colavecchia, Silvia Beatriz; Fernández, Bárbara; Jolly, Ana; Minatel, Leonardo; Hajos, Silvia Elvira; Paolicchi, Fernando; Mundo, Silvia Leonor (Elsevier, 2019)
Mycobacterium avium subspecies paratuberculosis (MAP) is the causative agent of ruminant paratuberculosis. The aim of this study was to evaluate the biological behavior of different Argentinean strains of MAP in two bovine infection models: macrophage (in vitro) and calf (in vivo) through the evaluation of early immune responses at the peripheral and local levels. Two MAP strains (A and C) were selected taking into account the different patterns of TNF-α and IL-10 secretion displayed by infected bovine macrophages in vitro. Two groups of calves were infected with 250 mg of total wet weight live MAP: strain A infected group (MA, n = 3), strain C infected group (MC, n = 2). Another group of animals was mock-infected (MI, n = 3). Infection was confirmed by MAP culture of feces and microscopic observation of granulomatous lesions in the gut tissue. All infected calves showed positive results in the DTH skin test. A significant increase in peripheral CD4CD25+ cells in MC group on day 150 was detected. The specific cellular immune response developed allowed the identification of the infection as early as 30 days in the MA group. However, the percentage of CD8CD25+ cells was significantly increased on day 120 in MC group. Significant differences between groups in proliferation and cellular responses were also detected in ileocecal lymph node samples. In summary, the strains of MAP employed herein induced differential immune responses in peripheral cells, in the proliferative responses and in cell functionality at the local level. Our findings support the hypotheses that the in vitro behavior displayed by macrophages could be a tool to identify differences among MAP strains infecting bovines and that the host-pathogen interactions occurring upon infection are dependent on the strain of MAP involved.